On the Possibility and Impossibility of a Theoretical Dialogue between Nietzsche and Lacan - Rivas, Rodrigo Farías (2024)
The present article examines contemporary scholarship attempting a theoretical convergence between Lacanian psychoanalysis and Nietzschean philosophy. The main positions, ideas and arguments of this scholarship are assessed. In doing so, the philosophical problem that immediately arises concerns the very possibility of such a theoretical dialogue. The thesis to be developed, then, is that superficial similarities rather obscure core theoretical, and even ontological, disagreements – and so besides the critical examination of the mentioned literature, the goal of the paper is to illuminate these tensions insofar they obstruct easy Nietzsche-Lacan articulations. Thus following the resemblances between both theoretical perspectives, we move from the merely superficial to the stronger similarities among the will to power, unconscious desire and jouissance, then between nihilism and jouissance, and finally between the very logics of resentment and repression. At each step, the article shows similarities to rather be insufficient, to the extent they are sustained on unquestioned assumptions. The paradigmatic one: the idea that Nietzsche is already a Lacanian avant la lettre.